Cultural Diplomacy of The Republic of Korea in The Middle East: A Netnographic Analysis of Jungkook BTS’s Performance at The Fifa World Cup 2022 - Maulida Ayu; Teuku Rezasyah; Deasy Silvya Sari (Eduvest - Journal of Universal Studies, 2024)
Jungkook from BTS (Bangtan Boys) made history as the first Asian singer to perform at the opening ceremony of FIFA World Cup 2022. While his performance symbolized a significant moment for the Korean wave and its role in Korean cultural diplomacy on the global stage, it drew criticism from some Western countries. This response stemmed from concerns about human rights issues in Qatar, such as the treatment of migrant workers involved in constructing Al-Bayt Stadium. This study aims to analyze the objectives of South Korea's cultural diplomacy in the Middle East through Jungkook’s appearance at the FIFA World Cup 2022 opening ceremony. Employing a netnographic approach, the research involved analyzing social media commentary, particularly by categorizing relevant keywords from Twitter (X) posts connected to this topic. Using frameworks in cultural diplomacy, constructivism, and nation branding, the study finds that Jungkook’s performance served to foster mutual understanding, strengthen international cooperation between Qatar and South Korea, establish a positive image in the Middle East, and further promote South Korea's nation branding on a global scale.